Optical investigations of interaction between zinc tetra phenyl porphyrin and CdSe nanoparticles - Lihitkar, N. B.; Singh, S. B.; Singh, Jai; Srivastava, O. N.; Naik, R. H.; Kulkarni, S. K. (Chemical Physics Letters, 2009)
Interactions between nanoparticles of zinc tetra phenyl porphyrin (ZnTPP) with CdSe nanoparticles in dimethyl sulphoxide solvent have been investigated. A ZnTPP-CdSe complex was formed which showed substantial changes in the UV-Vis absorption spectra in the presence of CdSe. Fluorescence measurements showed an interesting behavior at low as well as high concentrations of CdSe. When low concentrations of CdSe nanoparticles were added to the ZnTPP nanoparticles solution, besides two fluorescence bands due to ZnTPP nanoparticles, an intense new band appeared. On the other hand at high concentrations of CdSe one of the fluorescence band of ZnTPP at similar to 604 nm increased. (C) 2009 Published by Elsevier B. V.